Exposure to polycyclic aromatic hydrocarbons, heavy metals, and per- and polyfluoroalkyl substances and their associations with serum lipid profiles in the general Korean adult population - Sanghee Shin; Youlim Kim; Yunsoo Choe; Su Hwan Kim; Jaelim Cho; Changsoo Kim; Kyoung-Nam Kim (Environmental Health)
Abstract Background Previous studies on associations between polycyclic aromatic hydrocarbons (PAHs) and lipid profiles are limited. We investigated the associations between urinary PAH metabolites and serum lipid profiles using a representative sample of Korean adults. Methods This study utilized data from the Korean National Environmental Health Survey (2018–2020) (n = 2,516). The associations of PAH metabolites, heavy metals, and per- and polyfluoroalkyl substances (PFASs), which are ubiquitous pollutants, with lipid indicators and dyslipidemia types were evaluated using linear and logistic regression models, respectively. We examined the associations between a mixture of PAH metabolites, heavy metals, and PFASs and lipid profiles using quantile g-computation analyses. Results A doubling of 1-hydroxypyrene (1-OHP) concentrations was associated with higher total cholesterol (TC) [β = 2.50 mg/dL, 95% confidence interval (CI): 1.09, 3.91], low-density lipoprotein cholesterol (LDL-C) (β = 2.39 mg/dL, 95% CI: 1.14, 3.63), and non-high-density lipoprotein cholesterol (non-HDL-C) concentrations (β = 2.13 mg/dL, 95% CI: 0.77, 3.49). A doubling of 1-OHP concentrations was also linked to higher odds of high TC [odds ratio (OR) = 1.15, 95% CI: 1.02, 1.30]. Additionally, 2-naphthol concentrations were associated with higher odds of high TC (OR = 1.14, 95% CI: 1.00, 1.29) and high LDL-C (OR = 1.27, 95% CI: 1.06, 1.51). Lead concentrations were associated with higher levels of TC, LDL-C, non-HDL-C, and high-density lipoprotein cholesterol (HDL-C), as well as with higher odds of high TC, high LDL-C, and high non-HDL-C. Mercury concentrations were associated with higher levels of TC, LDL-C, and non-HDL-C, and with higher odds of high TC. Several PFASs, such as perfluorooctanoic acid, perfluorononanoic acid, and perfluorodecanoic acid, were also associated with lipid profiles. A mixture of PAH metabolites, heavy metals, and PFASs was associated with higher TC, LDL-C, non-HDL-C, and HDL-C concentrations. This mixture was also linked to higher odds of high TC and high LDL-C. Conclusion Concentrations of PAH metabolites, heavy metals, and PFASs were associated with unfavorable lipid profiles in the general adult population.